Konsep Pendidikan Akhlak Menurut Syekh Umar Bin Ahmad Baradja dalam Kitab Akhlak Lil Banin Relevansinya dengan Pendidikan Akhlak Masa Kini - Reza Nurul Fauziah; Sobar Al Ghazal; Eko Surbiantoro (Bandung Conference Series: Islamic Education, 2022)
Abstract. Human quality can not only be measured in terms of scientific excellence and expertise alone, but also measured by the quality of morals. High knowledge without being accompanied by noble character will be in vain. Knowledge without morality will lead to destruction. Various phenomena and social phenomena among people who are not good have become a daily scene. This degradation of children's behavior occurs because of the lack of moral education since childhood. Moral education should ideally be carried out in children from an early age in the context of inculcating moral values. This study aims to explore and describe the concept of moral education according to Sheikh Umar Baradja contained in the book Akhlak Lil Banin. This study uses qualitative methods while the type of research used is library research. The discussion is carried out based on a literature review as well as several articles that are relevant to the object of study being studied. Based on the results of the study, it is known that the concept of moral education according to Sheikh Umar Baradja is very relevant to the current moral education in view of the objectives, materials and methods presented in the book of Morals Lil Banin. The results of this study after an in-depth research study, show that the concept of moral education in the book of morals lil banin includes the importance of moral education from an early age, the basis of moral education in the Qur'an and Hadith, the objectives and methods of moral education, the scope of morals towards Allah SWT. , Rasulullah SAW, family, relatives, neighbors, society as well as various kinds of morals (morals and morals of mazmumah). Abstrak. Kualitas manusia tidak hanya dapat diukur dari segi keunggulan keilmuan dan keahlian semata, tetapi juga diukur dari kualitas akhlaknya. Ilmu yang tinggi tanpa disertai dengan akhlak yang mulia akan menjadi sia-sia. Ilmu tanpa akhlak akan membawa kepada kehancuran. Berbagai fenomena dan geja sosial dikalangan masyarakat yang kurang baik sudah menjadi pemandangan sehari-hari. Degradasi perilaku anak ini terjadi karena kurangnya Pendidikan akhlak sejak kecil. Penddikan akhlak idealnya dilakukan pada anak sejak usia dini dalam rangka penanaman nilai-nilai akhlak. Penelitian ini bertujuan untuk menggali dan mendeskripsikan konsep Pendidikan akhlak menurut Syekh Umar Baradja yang terdapat dalam kitab Akhlak Lil Banin. Penelitian ini menggunakan metode kualitatif sedangkan jenis penelitian yang digunakan adalah library research. Pembahasan dilakukan berdasarkan telaah Pustaka serta beberapa tulisan yang relevan dengan objek kajian yang diteliti. Berdasarkan hasil penelitian diketahui bahwa konsep Pendidikan akhlak menurut Syekh Umar Baradja sangat relevan dengan Pendidikan akhlak saat ini melihat dari tujuan, materi dna metode yang di sampaikan dalam kitab Akhlak Lil Banin. Hasil penelitian ini setelah dilakukan kajian penelitian yang mendalam, menunjukan bahwa konsep pendidikan akhlak dalam kitab akhlak lil banin mencakup pentingnya Pendidikan akhlak sejak dini, dasar Pendidikan akhlak Al-Qur’an dan Hadist, tujuan dan metode Pendidikan akhlak, ruang lingkup akhlak terhadap Allah SWT, Rasulullah SAW, keluarga, kerabat, tetangga, masyarakat serta macam-macam akhlak (akhlak mahmudah dan akhlak mazmumah).